2000
DOI: 10.1002/(sici)1097-4636(20000305)49:3<362::aid-jbm9>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among cell attachment, spreading, cytoskeletal organization, and migration rate for anchorage-dependent cells on model surfaces

Abstract: Many research and commercial applications use a synthetic substrate which is seeded with cells in a serum-containing medium. The surface properties of the material influence the composition of the adsorbed protein layer, which subsequently regulates a variety of cell behaviors such as attachment, spreading, proliferation, migration, and differentiation. In this study, we examined the relationships among cell attachment, spreading, cytoskeletal organization, and migration rate for MC3T3-E1 osteoblasts on glass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
145
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 231 publications
(157 citation statements)
references
References 33 publications
7
145
0
Order By: Relevance
“…In the case of SAMs, differences in cell attachment [39] as well as differences in myoblast differentiation [2] could be attributed to film chemistry and/ or wettability. The nature of the functional groups was indeed found to be the most important factor [40] . For all these reasons, small changes in (PLL/HA) film chemistry and wettability upon cross-linking are likely to play a minor role in the observed differences in cell behavior.…”
Section: Relative Importance Of Film Stiffness Roughness and Wettabimentioning
confidence: 92%
“…In the case of SAMs, differences in cell attachment [39] as well as differences in myoblast differentiation [2] could be attributed to film chemistry and/ or wettability. The nature of the functional groups was indeed found to be the most important factor [40] . For all these reasons, small changes in (PLL/HA) film chemistry and wettability upon cross-linking are likely to play a minor role in the observed differences in cell behavior.…”
Section: Relative Importance Of Film Stiffness Roughness and Wettabimentioning
confidence: 92%
“…The cells might spread up to 100 ÎŒm in size on the APTMS-coated substrates (Fig. 3c), and this effect is attributed to the chemical properties of the NH 2 + functional group of APTMS (Webb et al, 2000).…”
Section: Morphology Of Cho Cells On Different Substratesmentioning
confidence: 99%
“…Besides, cell migration also can be dominated by the chemical and physical properties of the substrates. For example, Webb et al found that the migration rate of MC3T3-E1 osteoblasts is significantly slower on the thiol surface compared with the oxidized thiol, quaternary amine and methyl surfaces [14]. Pelham & Wang [6] and Lo et al [15] showed that cell motility can be governed purely by the substrate rigidity.…”
Section: Introductionmentioning
confidence: 99%